2017
DOI: 10.1037/xlm0000417
|View full text |Cite
|
Sign up to set email alerts
|

Orthography affects second language speech: Double letters and geminate production in English.

Abstract: Second languages (L2s) are often learned through spoken and written input, and L2 orthographic forms (spellings) can lead to non-native-like pronunciation. The present study investigated whether orthography can lead experienced learners of English L2 to make a phonological contrast in their speech production that does not exist in English. Double consonants represent geminate (long) consonants in Italian but not in English. In Experiment 1, native English speakers and English L2 speakers (Italians) were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 19 publications
11
74
0
3
Order By: Relevance
“…L1 orthography affected L2 speakers' consonant duration in English, in line with previous findings. Both learners and late bilinguals produced the same English consonant as longer when it was spelled with double letters than when it was spelled with a single letter, whereas spelling did not affect native speakers' consonant duration, as found in previous studies (Bassetti 2017;Bassetti & al., under review). The learners' mean closure duration ratio of 1.43 was smaller than the ratios found by Bassetti (2017) with similar participants (1.66 in a word reading task, and 1.70 in two word repetition tasks), but both the learners' and the bilinguals' ratios were similar to the 1.38-1.39 ratios reported by Bassetti and colleagues (under review).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…L1 orthography affected L2 speakers' consonant duration in English, in line with previous findings. Both learners and late bilinguals produced the same English consonant as longer when it was spelled with double letters than when it was spelled with a single letter, whereas spelling did not affect native speakers' consonant duration, as found in previous studies (Bassetti 2017;Bassetti & al., under review). The learners' mean closure duration ratio of 1.43 was smaller than the ratios found by Bassetti (2017) with similar participants (1.66 in a word reading task, and 1.70 in two word repetition tasks), but both the learners' and the bilinguals' ratios were similar to the 1.38-1.39 ratios reported by Bassetti and colleagues (under review).…”
Section: Discussionsupporting
confidence: 74%
“…manner). Bassetti (2017) reported that L1 Italian learners of L2 English tend to produce consonants as longer if they are represented with double consonant letters than when they are represented with single consonant letters (e.g. in floppy vs copy), although the magnitude of the effect is smaller than reported for their L1: consonants spelled with double consonant letters were on average 1.66 times as long as consonants spelled with single consonant letters.…”
Section: Effects Of Orthography On Consonantal Lengthmentioning
confidence: 87%
See 2 more Smart Citations
“…Mais ajouter la visualisation des traits parlés par le support écrit développe la conscience phonologique plus efficacement, nous y reviendrons. Des recherches récentes montrent que l'exposition à l'input écrit a des effets positifs dans la prononciation en L2 (Escudero 2015 ;Bassetti, 2017). La norme agit conjointement, sur les choix parlés des acteurs ; la tendance au relâchement des syllabes ( ouais, j'sais) peut devenir une norme acceptable dans une situation privée.…”
Section: Didactique Et Phonétique : Des Légitimités Scientifiques Peuunclassified